USER EXPERIENCE AND DIGITAL ADAPTATION: A QUALITATIVE STUDY OF SHARING ENGLISH LEARNING ACTIVITIES ON TIK TOK AMONG FRESH GRADUATE TEACHERS - Salainti, Engelina; Rotikan, Reymond (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study explores the User Experience (UX) and digital adaptation of fresh-graduate English teachers using TikTok to share their experiences of learning activities. Although TikTok is primarily associated with entertainment, a growing number of novice educators are leveraging it as a professional instrument for educational vlogging. This research utilizes a qualitative descriptive approach to investigate the experiences of three recently graduated teachers. Data collection involved semi-structured interviews and observations of their digital content on the TikTok platform. The results reveal a significant shift in the teachers' viewpoints, evolving from a